Study on the microclimate and thermal comfort of urban parks under arid climate conditions: A case study of Shihezi City - Jie Li; Zhao Zhao; Hong Chen; Zongchi Fu (Case Studies in Thermal Engineering)
The climate of arid regions poses considerable challenges to thermal comfort, necessitating effective mitigation strategies. Urban parks play a crucial role in regulating microclimates and alleviating the urban heat island effect. This study employs the ENVI-met model to evaluate the influence of park landscape configurations on outdoor microclimates and thermal comfort. The findings indicate that greening, water coverage, and topography exhibit a strong negative correlation with PET (r = −0.9), thereby significantly enhancing both the microclimate and thermal comfort of parks and their surrounding areas. An increase in green coverage was found to reduce the maximum PET by 0.64 °C; however, excessive tree density hindered nighttime ventilation. Expanding water coverage from 10 % to 40 % lowered daytime PET from ‘very hot’ (>41 °C) to ‘hot’ (35–41 °C), although it led to a rise in nighttime PET. Trees provide better microclimate improvement than water bodies. Additionally, the most pronounced reduction in PET (0.11 °C) was observed on slopes within the 0–5° range, with a diminishing effect at steeper inclinations. Consequently, park design in arid regions should carefully regulate tree spacing, water body dimensions, and slope gradients, incorporating additional tree cover along extended slopes to optimize thermal comfort. This study provides empirical evidence to support the sustainable development of parks in arid regions such as Xinjiang, enhancing both park environments and their adjacent urban areas while improving overall livability for residents.